A phase I study of PankoMab-GEX, a humanised glyco-optimised monoclonal antibody to a novel tumour-specific MUC1 glycopeptide epitope in patients with advanced carcinomas. (August 2016) - Fiedler, W.; DeDosso, S.; Cresta, S.; Weidmann, J.; Tessari, A.; Salzberg, M.; Dietrich, B.; Baumeister, H.; Goletz, S.; Gianni, L.; Sessa, C.
Abstract: Background: A phase I open-label dose-escalation study was conducted to define the safety, tolerability, and pharmacokinetics (PK) of PankoMab-GEX, a glyco-optimised humanised IgG1, with high affinity to a novel tumour-specific glycopeptide epitope of MUC1 (TA-MUC1) with excellent preclinical anti-tumour activity. Patients and methods: Seventy-four patients with advanced TA-MUC1-positive carcinomas received PankoMab-GEX intravenously every 3 (Q3W), 2 (Q2W), or 1 (QW) week in doses of 1–2200 mg in a three-plus-three dose-escalation design until disease progression (NCT01222624 ). Results: No maximum tolerated dose was reached. Adverse events were mainly mild-to-moderate infusion-related reactions (IRRs) by the first infusion in 45% of patients. Only one dose-limiting toxicity, a grade III IRR, was observed. PankoMab-GEX exhibited linear PK over all doses. Mean terminal half-life was 189 ± 66 h (Q3W), without dose dependency. A target trough level ≥50 μg/mL was reached after one infusion with doses ≥1700 mg Q3W in 80% of patients. Clinical benefit in 60 evaluable patients included one complete response in a patient with ovarian cancer treated 483 d and confirmed disease stabilisation in 19 patients lasting a median (range) of 23 (10–109) weeks. All but two of the patients with clinical benefit had received a compounded total dose ≥700 mg over a 3-week period, including 8 of 12 (67%) patients with ovarian cancer. Conclusion: PankoMab-GEX is safe, well tolerated, and showed promising anti-tumour activity in advanced disease. A phase IIb study is ongoing evaluating the efficacy of PankoMab-GEX as a maintenance therapy in advanced ovarian cancer. Highlights: PankoMab-GEX is a glyco-optimised humanised IgG1 monoclonal antibody. It binds to a glycopeptide epitope on tumour-associated MUC1. Glyco-optimisation leads to enhanced tumour cell killing (antibody-dependent cell cytotoxicity, apoptosis). Phase I trial: PankoMab-GEX was safe, well tolerated, and of low immunogenicity. Anti-tumour activity in advanced disease, particularly in OvCa, was observed.